Nomenclatural adjustments in two South American species of Senecio (Compositae, Senecioneae) - Calvo, Joel; Morales-Fierro, Vanezza (Phytotaxa, 2021)
After the monographic revision of the genus Senecio Linnaeus (1753: 866) from Chile by Cabrera (1949), several nomenclatural adjustments were made (Jeffrey 1992, Soldano 1998, Calvo 2020, Wu et al. 2020). Herein, we point out the illegitimacy of two names that have widely been accepted in the literature dealing with Senecio in the Southern Cone of South America (Cabrera 1949, Cabrera 1971, Marticorena & Quezada 1985, Freire 2008, Freire et al. 2014, Rodríguez et al. 2018). The respective priority names are indicated. Moreover, the name S. crepidoides Philippi (1894: 252) is lectotypified.